EVERYBODY AND NOBODY: VISIONS OF INDIVIDUALISM AND COLLECTIVITY IN THE AGE OF AI. - SINNREICH, ARAM; LINGEL, JESSA; LICHFIELD, GIDEON; ROTTINGHAUS, ADAM RICHARD; AVI BROOKS, LONNY J. (ETC: A Review of General Semantics, 2015)
The article presents responses from authors including Aram Sinnreich, Jessa Lingel and Gideon Lichfield on the visions of collectivity and individualism in the age of artificial intelligence (AI). Topics include the relationship of individualism and collectivism in the contemporary society, the impact of science fiction on hybridism and change of narratives and the problem of human-machine consciousness.